The impact of social network use on adolescent depression: the chain mediation between self-objectification and body satisfaction - Tang, Yiming; Xu, Min; Tan, Zhongwei; Liu, Yong (Frontiers in Psychology, 2024)
Introduction Adolescents are in the transitional stage from childhood to adulthood, a critical period for individual physical and mental development. With the rapid development of the Internet, social networking has become an integral part of adolescents’ daily lives. However, the information that adolescents are exposed to on social networks is often processed and embellished, which may cause them to become physically dissatisfied and lead to emotional problems, such as depression. We investigated the chain-mediating effects of self-objectification and body satisfaction on the relationship between social network use and depression. Methods We utilized questionnaire data of 2025 adolescents from two secondary schools and one high school in China. Results Our results demonstrated that (1) there are obvious sex differences in the intensity of social network use and active and passive social network use among adolescents, with usage higher among girls than for boys; (2) self-objectification and body satisfaction play a mediating role in the relationship between the intensity of social network use and adolescent depression, as well as the presence of chain-mediating roles; and (3) self-objectification and body satisfaction play an intermediary role in the relationship between active and passive social network use and adolescent depression; there is further a chain intermediary role. The findings suggest that social network use affects adolescents’ depression through self-objectification and body satisfaction, which is not only manifested in the general use intensity of social networks but also in their active and passive use modes of social networks. Conclusion This study provides theoretical support for the causes and mechanisms behind the influence of social network use on adolescent depression and has practical implications for the prevention and intervention of adolescent emotional problems.